Nutritional evaluation of integral cassava root silages for growing pigs - Araújo, Diego D. [UNESP]; Amorim, Alessandro B.; Saleh, Mayra A.D. [UNESP]; Curcelli, Felipe [UNESP]; Perdigón, Pedro L.; Bicudo, Silvio J. [UNESP]; Berto, Dirlei A. [UNESP] (Elsevier, 2016)
The experiment aimed at determining the nutritional value of integral cassava root silages with yogurt as inoculant or wastewater (manipueira) by liquid addition ensiling process. Eighteen crossbred piglets (Large White × Landrace), castrated males with an initial average weight of 50 kg were allocated in metabolism cages throughout 11-day trial duration (6 days for animal's adaptation to the cages and to the experimental diets, and 5 days of urine and faeces collection). The experimental design was a randomized block arrangement with 3 treatments and 6 replicates: basal diet (100%); mixture composed of 75% basal diet and 25% integral cassava root silage with yogurt as inoculant; a mixture composed of 75% of basal diet and 25% integral cassava root silage with wastewater. The silages with wastewater and yogurt presented the following values of apparent digestibility of dry matter 89.96% and 90.01%, apparent digestibility of crude protein of 60.67% and 66.43%, apparent digestibility of gross energy of 90.43% and 91.48%, gross energy metabolizability coefficients of 87.88% and 88.93%, digestible energy values of 3,705 and 3,783 kcal/kg on a dry matter (DM) basis, and metabolizable energy values of 3,600 and 3,676 kcal/kg DM, respectively. The results have demonstrated that integral cassava root silages with wastewater or yogurt have a high nutritional value and can be used as an alternative energy source in growing pig's diets.
Keywords: Alternative feed; Digestibility; Energy sources; Ensiling; Swine